2011
DOI: 10.1007/s11307-011-0475-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhaled Gases on Ultrasound Contrast Agent Longevity In Vivo

Abstract: PurposeThe purpose of this study is to investigate the effect of the inhaled gas used alongside isoflurane in the anesthetization of small animals on the time-intensity curves (TICs) acquired from ultrasound contrast agents—microbubbles.ProceduresTICs were recorded over the common iliac vein of 12 mice receiving Definity®. Animals were anesthetized with isoflurane, the ventilator was driven by medical air (MA), then in random order, the driving gas was changed for 3 min to: MA (control); pure oxygen (O2); O2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…We posited that different vascular effects induced by these two protocols may have had an impact on the interactions between the ultrasound field, the microbubbles, and the brain microvasculature. Around the same time, two studies were published showing that the circulation time for ultrasound contrast agents was substantially reduced when subjects were breathing oxygen compared to medical air (Mullin et al 2011; Itani and Mattrey 2011), which could also explain our results.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We posited that different vascular effects induced by these two protocols may have had an impact on the interactions between the ultrasound field, the microbubbles, and the brain microvasculature. Around the same time, two studies were published showing that the circulation time for ultrasound contrast agents was substantially reduced when subjects were breathing oxygen compared to medical air (Mullin et al 2011; Itani and Mattrey 2011), which could also explain our results.…”
Section: Introductionsupporting
confidence: 54%
“…Others have found that microbubble circulation times were reduced in animals breathing oxygen compared to medical air (Mullin et al 2011; Itani and Mattrey 2011). The results of the present study demonstrate that oxygen can have a profound diminutive effect on BBB disruption and suggests that our earlier study was not due to anesthesia, but instead to the use of oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such methods the quantification of bound tMBs strongly depends on the injected dose, imaging system gain, and local perfusion [137]. In addition, the influence of inhaled gases in the anaesthetic protocols influences the MBs longevity [148][149][150][151]. These studies confirmed longer circulation times of in-house lipid-shell decafluorobutane-filled UCAs and commercially available UCAs such as Definity and Albunex when animals breathe medical air instead of pure oxygen as the carrier gas for the isoflurane anaesthetic.…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 76%
“…In one study, the decay rate on time-intensity curves measured with ultrasound imaging was almost three times higher when oxygen was used as the carrier gas for isoflurane than when medical air was used (Itani and Mattrey 2011). Another study also found a statistically significant improvement in persistence in microbubble circulation with medical air compared to oxygen as the carrier gas (Mullin et al 2011).…”
Section: Introductionmentioning
confidence: 99%